IMPLEMENTASI PENGEMBANGAN KECERDASAN INTRAPERSONAL SISWA MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA - Ramadhan, Putri Utami; Aziz, Lutfi Abdul (ISLAMIKA, 2022)
The current phenomenon in the world of education is indicated by the fact that there are still many students who are passive in the learning process because they feel less confident, do not participate in learning activities, and do not dare to express their own opinions and arguments. To overcome this phenomenon, students must develop intrapersonal intelligence. This is in accordance with the objectives of Pancasila Education and Learning, namely developing each potential student into a person who has a close relationship with Pancasila values. The purpose of this research is to learn more about how to implement the development of students' intrapersonal intelligence through Pancasila Education. The methodology in this study is to use a qualitative approach with descriptive methods. The results showed that in learning Pancasila Education, there was the development of students' intrapersonal intelligence through the application of contextual learning strategies and independent assignment methods, providing space for students to dare to express opinions, giving rewards, as well as supporting activities and habituation, namely getting used to disposing of trash in its place, and giving advice and motivation to students. Furthermore, almost all of the material in learning Pancasila Education contains the development of intrapersonal intelligence. Keywords: Implementation, Learning Pancasila Education, Intrapersonal Intelligence